Nutritional status of patients with pleural empyema - Książek, Janina; Wernerowska, Justyna; Chwirot, Piotr (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. Management of pleural empyema represents one of the biggest challenges in thoracic surgery, as this condition is a frequent complication of various diseases, requires long hospitalization and generates high therapeutic costs. Aim. The aim of the study was to analyze the nutritional status of patients with pleural empyema, hospitalized at the Department of Thoracic Surgery, University Clinical Center (UCC) in Gdansk. Material and methods. The study included 50 patients hospitalized at the UCC’s Department of Thoracic Surgery. The study was based on a diagnostic survey, review of literature, analysis of medical documentation, and statistical analysis. The protocol of the study was approved by the Local Bioethics Committee (decision no. NKBBN/82/2013). The patients were examined with a survey and took part in the Subjective Global Assessment of Nutritional Status (SGA). The results were analyzed with Statistica® 10 package. Statistical hypotheses were verified with multifactorial ANOVA. Results and conclusions. On the basis of subjectively assessed number and severity of symptoms included in the SGA, four patients were diagnosed with cachexia and one person turned out to be at increased risk of undernutrition. A total of 10% of the patients assessed their nutritional demands as high. Analysis of nutritional status of patients with pleural empyema requires interdisciplinary solutions and meticulous psychological analysis.